Dolphin Morbillivirus in a Cuvier’s Beaked Whale (Ziphius cavirostris), Italy - Centelleghe, Cinzia; Beffagna, Giorgia; Palmisano, Giuseppe; Franzo, Giovanni; Casalone, Cristina; Pautasso, Alessandra; Giorda, Federica; Di Nocera, Fabio; Iaccarino, Doriana; Santoro, Mario; Di Guardo, Giovanni; Mazzariol, Sandro (Frontiers in Microbiology, 2017)
Dolphin morbillivirus (DMV) has caused several mortality events in Mediterranean striped (Stenella coeruleoalba) and bottlenose (Tursiops truncatus) dolphins populations since nineties; in the last 5 years, the virus was reported to infect new hosts in this basin, such as fin whales (Balaenoptera physalus), sperm whales (Physeter macrocephalus) and even a harbor seal (Phoca vitulina). Very recently, a calf Cuvier’s beaked whale (Ziphius cavirostris) calf stranded on the Southern Italian coastline with mild pathological findings suggestive of morbilliviral infection, received the first confirmation of DMV infection in this species by biomolecular evidences on lung tissue. This new cross species infection report, along with 19% of the cetaceans specimens examined by the Italian Stranding Network being found positive to DMV, support the hypothesis of an endemic circulation of this virus among Mediterranean cetaceans.